Tinjauan Pustaka Faktor Risiko Penyebab Terjadinya Hepatoseluler Karsinoma Akibat Hepatitis B - Gitana Gezatania; Suzanna Ndraha; Marcel Antoni (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
Hepatitis B is a liver infection caused by the hepatitis B virus (HBV) which has the potential to threaten a person's life. According to WHO, hepatitis B is a major global health problem that causes acute and chronic infections. Chronic hepatitis B has a very high risk of developing hepatocellular carcinoma. The purpose of writing this literature review is to determine the risk factors for the occurrence of hepatocellular carcinoma in someone who is infected with HBV. Methods of data collection through the Pubmed website, Wiley Online Library, and Springer Link from 2012-2022, 10 journals were found to be analyzed in writing this literature review. From the 10 journals analyzed, it can be concluded that type 2 diabetes mellitus in someone who is infected with HBV is an important risk factor that increases the risk of developing hepatocellular carcinoma.